Human and Economic Cost of Disease Burden Due to Congenital Hypothyroidism in India: Too Little, but Not Too Late - Vidavalur, Ramesh (Frontiers in Pediatrics, 2022)
Background: Congenital hypothyroidism (CH) is one of the most common preventable causes of mental retardation. Implementing newborn screening (NBS) in >52 countries enabled early detection and to initiate treatment of neonates with CH. India is yet to implement national NBS program even though estimated 5-15% of sick newborns suffer from genetic and metabolic disorders. Recent pilot studies confirm the CH incidence rates range from 1 in 500 to 1 in 3400 live births. Our objective was to estimate overall incidence rates of congenital hypothyroidism and to evaluate the costs and benefits of implementing universal NBS for CH in India. Methods: We used best available epidemiological and cost data to synthesize incidence rates and screening costs for CH in India. We used two models to estimate intellectual disability in unscreened cohorts. Disability-adjusted life years (DALY) were calculated to quantify burden of disease utilizing disability weights. Direct costs including screening, confirmatory tests and treatment costs were obtained from public and private market sources. Economic benefits were calculated from lost DALY using human capital approach and value of statistical life methods, . Cost discounting used to estimate present value of future benefits over lifetime of affected newborns. Results: Estimated annual incidence ranged from 14,000-20,730 cases and those at risk for intellectual disability ranged from 5,397-13,929 cases. Estimated discounted and undiscounted lost DALYs were 57,640 and 410,000, respectively. Direct annual costs for universal screening for CH in India is around USD187 million. Based on current incidence and expected severity of sequelae, economic losses ranged from USD 159 million to 1.1 billion. Benefit-cost ratios ranged from 1.8 to 6. Conclusions: Universal NBS for CH is one of the healthcare interventions that is beneficial to prevent morbidity and cost saving. The economic benefits, derived from prevention of intellectual disability, assuming cost effectiveness threshold of three times of gross domestic product per capita, far outweigh the direct and indirect costs of screening, treatment and surveillance throughout the life of the affected individuals. Our analysis strongly supports the argument for investing in NBS that provides good value for money and would yield substantial financial gains for the country.